Strain Rate Dependent Behavior of Vinyl Nitrile Helmet Foam in Compression and Combined Compression and Shear - Nicolas Bailly; Yvan Petit; Jean-Michel Desrosier; Olivier Laperriere; Simon Langlois; Eric Wagnac (Applied Sciences, 2020)
Vinyl nitrile foams are polymeric closed-cell foam commonly used for energy absorption in helmets. However, their impact behavior has never been described in isolation. This study aims to characterize the strain rate dependent behavior of three VN foams in compression and combined compression and shear. Vinyl nitrile samples of density 97.5, 125, and 183 kg/m3 were submitted to quasi-static compression (0.01 s−1) and impacts in compression and combined compression and shear (loading direction of 45°). For impacts, a drop test rig was used, and a method was developed to account for strain rate variation during impactor deceleration. Young’s modulus and stress at plateau were correlated with foam density in both compression and combined loading. Vinyl nitrile foams were strain rate dependent: The absorbed energy at the onset of densification was two to four times higher at 100 s−1 than at 0.01 s−1. In combined loading, the compressive stress at yield was reduced by 43% at a high strain rate. Compared to expanded polypropylene, vinyl nitrile foams transmitted less stress at the onset of densification for equivalent absorbed energy and presented a larger ratio between the compression and shear stresses in combined loading (0.37 at yield). This larger ratio between the compression and shear stresses might explain why vinyl nitrile helmet liners are thought to be better at reducing head rotational acceleration than expanded polypropylene helmet liners.